2015
DOI: 10.4269/ajtmh.14-0459
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differentiation of Treponema pallidum Subspecies in Skin Ulceration Clinically Suspected as Yaws in Vanuatu Using Real-Time Multiplex PCR and Serological Methods

Abstract: Abstract. We developed a TaqMan-based real-time quadriplex polymerase chain reaction (PCR) to simultaneously detect Treponema pallidum subspecies pallidum, T. pallidum subsp. pertenue, and T. pallidum subsp. endemicum, the causative agents of venereal syphilis, yaws, and bejel, respectively. The PCR assay was applied to samples from skin ulcerations of clinically presumptive yaws cases among children on Tanna Island, Vanuatu. Another real-time triplex PCR was used to screen for the point mutations in the 23S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 18 publications
2
65
1
Order By: Relevance
“…It was anticipated that the inclusion of those with this sign alone would lead to a prohibitively large number of RDTs being required, although in hindsight this would have only required a total of 22 RDTs (children with either bony swellings or skin lesions or both)—a finding that may guide future clinical/RDT surveys. Only 40% of children with skin lesions clinically consistent with yaws had a positive RDT, in keeping with a study conducted in Tafea province in 2013, in which 35.5% of children with clinically suspected yaws had positive serology [41]. These findings suggest that relying only on clinical diagnosis of yaws is insufficient and efforts should be made to increase access to RDTs.…”
Section: Discussionsupporting
confidence: 71%
“…It was anticipated that the inclusion of those with this sign alone would lead to a prohibitively large number of RDTs being required, although in hindsight this would have only required a total of 22 RDTs (children with either bony swellings or skin lesions or both)—a finding that may guide future clinical/RDT surveys. Only 40% of children with skin lesions clinically consistent with yaws had a positive RDT, in keeping with a study conducted in Tafea province in 2013, in which 35.5% of children with clinically suspected yaws had positive serology [41]. These findings suggest that relying only on clinical diagnosis of yaws is insufficient and efforts should be made to increase access to RDTs.…”
Section: Discussionsupporting
confidence: 71%
“…PCR techniques are increasingly used; however, there is as yet no commercially available or internationally approved test for T. pallidum 13 . Species-specific and subspecies-specific T. pallidum PCR testing is a developing technology that is still primarily available in research laboratories 127,128 , although these tests are anticipated to be more widely available in the near future. A systematic review and meta-analysis concluded that T. pallidum PCR was more efficient for confirmation than to exclude syphilis diagnosis in lesions 129 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Sampling procedures like swabbing for detection of Mycobacterium ulcerans ,[26] and Treponema pallidum subsp. pertenue [27] can be performed in the field. Routine diagnosis of CL is based on detection of Leishmania spp.…”
Section: Description Of Integrated Idm Ntd Implementationmentioning
confidence: 99%